Amazonian Spanish language contact and evolution - Fafulas, Stephen (Issues in Hispanic and Lusophone linguistics ;, 2020)
"Amazonian Spanish: Language contact and evolution explores the unique origins, linguistic features, and geo-political situation of the Spanish that has emerged in the Amazon. While this region boasts much linguistic diversity, many of the indigenous languages found within its limits are now being replaced by Spanish. This situation of language expansion, contact, and bilingualism is reshaping the sociolinguistic landscape of the Amazon by creating a number of Spanish varieties with innovative linguistic features that require closer scholarly attention. The current book documents this situation in detail. The chapters in this volume include work on distinct geographical regions of the Amazon, with primary data collected using different methodologies and language contact situations. The scholars in this volume specialize in an array of fields, including anthropological linguistics, bilingualism, language contact, dialectology, and language acquisition. Their work represents both formal and functional approaches to linguistics"--